Hepatitis C. Issue 2 (February 2018) - Dawson, Stacey; Meader, Emma
Hepatitis C virus (HCV) infection affects approximately 180 000 000 people worldwide, with the highest rates reported in Africa and Asia. In the UK, the rate is in the region of 1% of the population. Most infections become chronic and can lead to extensive liver damage and hepatocellular carcinoma. Despite recent advances in treatment strategies the high cost, high demand, screening uptake and re-infection rates make HCV one of the greatest healthcare challenges of modern medicine. This article provides an overview of HCV and aims to equip GPs for their role in screening and management in primary care.